(untitled) (The Research of Medical Science Review, 2024)
Objective: To explore the current evidence on the role of partial body weight support treadmill training (PBWSTT) to improve gait, walking ability and daily living activities after chronic stroke. Methods: A systematic review was conducted. We searched the relevant literature from 2003 to August 2020 by hand searching and from Cochrane, PubMed, Pedro and MEDLINE with proper search strategy develop as PICO format and Boolean operator. We found 13 studies on the use of PBWSTT on gait, walking outcomes in persons with chronic stroke and one on the quality of life outcome. Risk bias tool was used to evaluate the biasness in studies and Critical review form was used to evaluate the methodology quality of studies. Results: Total of 13 studies were included for assessment based eligibility. All studies were Randomized controlled trials. All studies lies between 11 to 15 score of Critical review form which showed high quality of methodology. Only one study targeted the quality of life outcomes other 12 studies not evaluate the quality of life outcome improvement after PBSWTT. Risk of bias in term of selection bias and detection bias was varies in all studies. Conclusion: This systematic review concluded that all studies support that partial body weight support treadmill training in improve walking ability and gait in persons with chronic. Study can’t conclude that partial body weight support treadmill training improve quality of life because only one study found in favor other studies not assessing the quality of life with walking and gait outcomes.